The essay as a learning tool and strategy - Segarra-Báez, Iván (2019)
The present work tries to innovate the area of higher education through the study of the benefits that the writing of the essay presents as a pedagogical tool and strategy in the higher education level of Puerto Rico. We continually observe language teachers the great difficulties that students present in their main years of university education because they do not know many of the basic tools for efficient writing. The proposal that defends this research is the efficient writing using the argumentative essay and its preparation in the academic teaching classroom.